(untitled) (Journal of Medical & Health Sciences Review, 2025)
Uterine fibroids are one of the most common benign tumors affecting women of reproductive age, often leading to a variety of gynecological and reproductive health concerns. While numerous risk factors have been identified, the role of vitamin D deficiency has recently emerged as an area of interest. This study explores the correlation between serum 25-hydroxyvitamin D (25OHD) levels and the presence of uterine fibroids through a case-control approach. Utilizing statistical models such as correlation and regression analysis, we assess the relationship between vitamin D levels and fibroid prevalence. Our findings highlight a significant inverse correlation between vitamin D levels and fibroid presence, suggesting that adequate vitamin D levels may play a role in fibroid prevention. These insights could lead to potential non-surgical interventions for managing this condition.